Membangun Karakter Melalui Tradisi: Integrasi Kearifan Lokal dalam Pembelajaran IPAS untuk Siswa Sekolah Dasar: Membangun Karakter Melalui Tradisi: Integrasi Kearifan Lokal dalam Pembelajaran IPAS untuk Siswa Sekolah Dasar - Innayah Wulandari; Eko Handoyo, Mintarsih Arbarini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe how the integration of local wisdom values through tradition can shape students' character in Natural and Social Sciences (IPAS) learning in elementary schools. In facing the challenges of globalization that have the potential to erode the noble values of the nation, character education based on local culture is very important to strengthen students' identity and morality from an early age. This study employs a descriptive qualitative approach with fourth and fifth-grade students at SDN 01 Baturejo, Sukolilo, Pati Regency as subjects. Data were collected through classroom observations, in-depth interviews, and documentation studies of local wisdom-based learning modules. The results of the study indicate that local traditions such as Meron and the folk tale of Syekh Jangkung can be used as effective IPAS learning media in instilling character values such as cooperation, responsibility, honesty, and environmental awareness. Teachers felt assisted in delivering the material because students were more enthusiastic and easily understood the concepts presented contextually. Students also demonstrated positive behavioral changes and pride in local culture. Thus, the integration of local wisdom in IPAS learning has proven to strengthen students' character and make the learning process more meaningful and relevant.